Oxford international lower secondary science student book 1 for grade 6 - Barber, Alison (Karachi Oxford university press, 2023)
The Oxford International Lower Secondary English Student Workbook 2 for Grade 6 is designed to support and reinforce the learning objectives outlined in the corresponding student book. It offers a wide range of exercises and activities that help students practice and apply their English language skills in areas such as reading comprehension, writing, grammar, and vocabulary. The workbook emphasizes the development of critical thinking, creativity, and communication skills, aligning with international educational standards. Each unit includes tasks that challenge students to analyze texts, construct well-structured responses, and engage in reflective learning. This workbook serves as an essential tool for students to consolidate their understanding, track their progress, and prepare for more advanced levels of English study.